CODIMENSION-TWO BIFURCATIONS IN INDIRECT FIELD ORIENTED CONTROL OF INDUCTION MOTOR DRIVES - SALAS, F.; GORDILLO, F.; ARACIL, J.; REGINATTO, R. (International journal of bifurcation and chaos in applied sciences and engineering, 2008)
This paper provides further results on bifurcation analysis of indirect field oriented control of induction motors. Previous results presented on this subject [Bazanella & Reginatto, 2000, 2001; Gordillo et al., 2002] are summarized and extended by means of a codimension-two bifurcation analysis. It is shown that codimension-two bifurcation phenomena, such as a Bogdanov–Takens and zero–Hopf bifurcations, occur in IFOC as a result of parameter mismatch and certain setting of the proportional-integral speed controller. Conditions for the existence of such bifurcations are derived analytically, as long as possible, and bifurcation diagrams are presented with the help of simulation and numerical bifurcation analysis.